2006
DOI: 10.1021/jp0563989
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of 1-Butyl-3-methylimidazolium Br-, I-, PF6-, BF4-, (CF3SO2)2N-, SCN-, CH3SO3-, CH3SO4-, and (CN)2N- Ionic Liquids by Sum Frequency Generation

Abstract: Sum frequency generation spectroscopy, SFG, was used for the surface characterization at the gas-liquid interface of the 1-butyl-3-methylimidazolium cation combined with the following anions: Br-, I-, PF6-, BF4-, (CF3SO2)2N- (imide), SCN-, CH3SO3- (MeSO3), CH3SO4- (MS), and (CN)2N- (DCN). The SFG spectra obtained for the different ionic liquids were similar independent of the anion selected; therefore, a comprehensive analysis for the surface characterization of the ionic liquids' cation was focused only on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
206
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(232 citation statements)
references
References 63 publications
21
206
5
Order By: Relevance
“…[80][81][82] Lithium bis(trifluoromethanesulfonyl)imide (99 %) was purchased from Iolitec; 1-ethyl-2,3 dimethylimidazolium chloride (! 98 %) and N,N,N-trimethyl-N-butylammonium chloride (98 %) were from Merck; 1-decylbromide (98 %), 1-methylimidazole (99 %), ethanol (p.a.…”
Section: Methodsmentioning
confidence: 99%
“…[80][81][82] Lithium bis(trifluoromethanesulfonyl)imide (99 %) was purchased from Iolitec; 1-ethyl-2,3 dimethylimidazolium chloride (! 98 %) and N,N,N-trimethyl-N-butylammonium chloride (98 %) were from Merck; 1-decylbromide (98 %), 1-methylimidazole (99 %), ethanol (p.a.…”
Section: Methodsmentioning
confidence: 99%
“…[273] Combined analysis by XPS and other surface analysis techniques including sum frequency generation, Rutherford backscattering spectroscopy, reflected infrared spectroscopy, and X-ray reflectivity have revealed the composition and structure of IL surfaces. [278][279][280][281] Furthermore, ultraviolet photoemission spectroscopy of ILs under vacuum conditions, which was first conducted by Yoshimura et al [282] , revealed the electronic structures of ILs in detail. [275,282,283] ILs possess negligible volatility at room temperature, but vaporization of some ILs was recognized by heating them under ultrahigh vacuum conditions.…”
Section: Analyses Under Vacuum Conditionsmentioning
confidence: 99%
“…Since the C2 proton is the one that presents the shortest H-Cl distance, 31 we assign the feature at 3016 cm 1 to the C2-H stretching mode and the other two features to the H-C4C5-H (asym) and H-C4C5-H (sym) stretching modes, respectively. Rivera-Rubero and Baldelli 36 have investigated the IR and Raman spectrum of IL derived from BMI C and different anions and also the deuterated forms of BMI C . The bands at 3110, 3160, and 3185 cm 1 observed in the Raman spectrum of BMIPF 6 were assigned to the C2-H, H-C4C5-H (sym) and H-C4C5-H (asym) stretching modes, respectively.…”
Section: The Raman Spectra Of Bmicl/nbcl 5 Ionic Mixturesmentioning
confidence: 99%
“…Figure 7 shows the observed shift in the Raman wavenumbers corresponding to the H-C4C5-H (sym) stretching near 3150 cm 1 and the C-H stretching of the CH 3 (butyl) 36 at ca 2956 cm 1 as a function of the X ZnCl 2 . Note that in both cases, there is a shift to higher wavenumbers as X ZnCl 2 increases, suggesting that the interaction of anionic species with these protons are decreasing as the X ZnCl 2 increases.…”
Section: The Raman Spectra Of Bmi/zncl 2 Ionic Mixturesmentioning
confidence: 99%